TRADISI AL-QUR’AN DALAM FENOMENA PENAFSIRAN - Hadi Mutamam (IBDA` : Jurnal Kajian Islam dan Budaya, 2015)
This study examines the tradition of the Koran in the phenomenon of the interpretation to be the basis for action. Al-Qur'an as the sacred scriptures of Islam contains many interesting things, one of which is stressed to live a way of life that is in harmony with Islam. Through studying the Koran with phenomenology that linking events with one another, then we can know the basic history and its impact. All that could be a lesson for the present life. Rules of life as lived by Muslims have the real truth in the Koran if they want to run in accordance with the Shari'a. Assessing the Koran as the basis for action is expected to have a good appreciation of the essence of life. This study found that the Koran is the basis for Muslims, as the law to determine the good and bad that create justice, to act in practice which will bring salvation.